Cardiovascular effects of medetomidine and cetamine in Puma concolor and recovery time after application of ioimbin or atipamezole - Caramalac, S. M.; Oliveira, A. R. [UNESP]; Albuquerque, V. B.; Deco-Souza, T.; Frazilio, F. O. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The aim of this study was to evaluate the cardiorespiratory changes caused by ketamine-associated medetomidine, and the recovery time after intramuscular application of atipamezole or yohimbine in Puma concolor. For this, the application of medetomidine (100 mu g/kg) associated with ketamine (5mg/kg) was performed in eleven brown ounces, and the cardiorespiratory parameters were recorded every 15 minutes during 90 minutes of evaluation. Afterwards, anesthesia was reversed with intramuscular application of yohimbine (0.4mg/kg; n=5) or atipamezole (0.25mg/kg; n=6), and time to recovery was analyzed. Of the cardiorespiratory parameters evaluated, there was a difference only in respiratory rate (between 60 and 90 minutes), however, within the reference range for the species. In addition, there was a significantly shorter time for sternal decubitus in the animals of the atipamezole group (18 +/- 7 minutes) when compared to the yohimbine group (36 +/- 17 minutes), however the complete recovery time was statistically equal between the two reversers analyzed. Thus, the anesthetic association promoted efficient, safe and fast induction anesthesia in puma, allowing the animals to be immobilized during the 90 minutes of evaluation without complications. Comparing anesthetic reversal with atipamezole and yohimbine, drug equivalence was observed in the complete recovery time of the animals.
Keywords: alpha-2 adrenergic agonists; wild animals; tranquilization